Kepercayaan (Trust) Terhadap Pengurus Organisasi dan Komitmen Afektif pada Organisasi Mahasiswa Daerah di Yogyakarta - Melisa Dwi Putri; Erika Setyanti Kusumaputri (Jurnal Psikologi Integratif, 2014)
Penelitian ini bertujuan untuk mengetahui hubungan antara kepercayaan terhadap komitmen afektif. Subjek penelitian ini adalah mahasiswa daerah yang berada di Yogyakarta dan tergabung dalam organisasi mahasiswa daerah. Metode pengumpulan data menggunakan skala komitmen afektif dan skala kepercayaan. Data dianalisis dengan teknik korelasi product moment dari Pearson dengan SPSS 16.0 for windows. Hasil penelitian menunjukkan terdapat hubungan positif antara kepercayaan terhadap pengurus organisasi dengan komitmen afektif pada organisasi mahasiswa daerah di Yogyakarta dengan nilai r 0,758 dan p = 0.000 (p < 0.05). Kata kunci: komitmen afektif, kepercayaan, mahasiswa daerah ABSTRACT This research is written to know the possitive relation between trust and affective commitment. The independent variable that is used in this research is trust, and the dependent variable is affective commitment. The subject in this research is local student organizations in Yogyakarta. Method of collecting data that is used in this research is scale of affective commitment and scale trust, all of the data that the writer get are analyzed by statistical analysis SPSS 16.0. for windows. Quantitative data is analyzed by product moment analysis technique. The result shows that there is positive relation significant between trust variable and affective commitment in local student organizations in Yogyakarta. The result of data analysis is correlation coefficient with r as 0,758 with p = 0.000 (p < 0.05). It means that there is significant positive relation between trust with affective commitment in local student organizations in Yogyakarta, which higher the trust of a local student organizations is higher the affective commitment. It also means that the lower trust of a local student organizations is lower the affective commitment. Keyword: Affective commitment, trust, local student organizations